VALIDITAS DAN PRAKTIKALITAS MEDIA VIDEO PEMBELAJARAN LAJU REAKSI PADA PLATFORM YOUTUBE UNTUK MENINGKATKAN KEMAMPUAN LITERASI KIMIA SISWA - J, Nurul Maulidia; Andromeda, Andromeda (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
The development of science and technology requires innovation in education to align with the needs of the 21st century. The government, through the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek), has implemented the Merdeka Curriculum, which positions students as the main subjects in the learning process. The Merdeka Belajar concept emphasizes a fun and pressure-free learning atmosphere that encourages students’ creativity and innovation. The use of technology, such as audio-visual–based learning videos, serves as an alternative to improve conceptual understanding, particularly through the YouTube platform, which is familiar and easily accessible to students. This study aims to develop a reaction rate learning video based on chemical literacy using the Plomp model, limited to the preliminary investigation and the development/prototyping stages. In the first prototype stage, a learning video was produced and then validated by three chemistry lecturers from Universitas Negeri Padang and two high school chemistry teachers. The validation results showed an Aiken’s V index of 0.89, categorized as valid. The practicality test conducted by teachers and students obtained an average score of 91.4%, categorized as very practical. The quiz evaluation results showed an improvement in students’ chemical literacy skills with an average score of 89, indicating that students were able to understand reaction rate concepts, identify natural phenomena, and solve mathematical problems related to reaction order and rate equations. Thus, the YouTube-based reaction rate learning video was declared valid, practical, and effective in improving students’ chemical literacy skills. ABSTRAKPerkembangan ilmu pengetahuan dan teknologi menuntut inovasi dalam pendidikan agar selaras dengan kebutuhan abad ke-21. Pemerintah melalui Kemendikbudristek menerapkan Kurikulum Merdeka yang menempatkan peserta didik sebagai subjek utama dalam pembelajaran. Konsep Merdeka Belajar menekankan suasana belajar yang menyenangkan dan bebas tekanan sehingga mendorong kreativitas serta inovasi peserta didik. Pemanfaatan teknologi seperti video pembelajaran berbasis audio-visual menjadi alternatif untuk meningkatkan pemahaman konsep, terutama melalui platform YouTube yang dekat dengan siswa dan mudah diakses. Penelitian ini bertujuan mengembangkan video pembelajaran laju reaksi berbasis literasi kimia menggunakan model Plomp yang dibatasi pada tahap investigasi awal serta pengembangan dan pembentukan prototipe. Pada tahap pengembangan prototipe I dihasilkan video pembelajaran yang kemudian divalidasi oleh tiga dosen kimia Universitas Negeri Padang dan dua guru kimia SMA. Hasil validasi menunjukkan nilai Aiken’s V sebesar 0,89 dengan kategori valid. Uji kepraktisan oleh guru dan peserta didik memperoleh rata-rata 91,4% dengan kategori sangat praktis. Hasil evaluasi kuis menunjukkan peningkatan kemampuan literasi kimia dengan nilai rata-rata 89, yang menandakan siswa mampu memahami konsep laju reaksi, mengidentifikasi fenomena alam, serta menyelesaikan persoalan matematis pada orde dan persamaan reaksi. Dengan demikian, video pembelajaran laju reaksi berbasis YouTube dinyatakan valid, praktis dan mampu meningkatkan kemampuan literasi kimia peserta didik.